(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Classical literature, much like mathematical constants, has long served as the foundational structure in the literary universe. Yet, as societies evolve, these constants are being re-evaluated, challenged, and reinterpreted. Contemporary retellings of canonical works signify a dynamic literary process—akin to transforming a linear equation into a multi-variable function—where fixed narratives are adapted to express a broader, more inclusive range of experiences. This article explores how modern authors reimagine classical texts to reflect present-day concerns such as gender equity, postcolonial identity, and social justice. Through the lens of adaptation theory and intertextuality, the article examines key examples where retellings not only preserve the thematic essence of the original but also challenge its limitations. For instance, Madeline Miller’s The Song of Achilles reconfigures Homeric heroism into a poignant queer love story, thereby adding emotional dimensions that were historically unexpressed. Similarly, Divakaruni’s The Palace of Illusions reconstructs the epic Mahabharata from Draupadi’s viewpoint, subverting patriarchal norms embedded in the original while retaining its narrative integrity. These texts act like literary matrices—maintaining the structure but allowing new values to enter the system. Contemporary retellings do not replace the classics; rather, they act as iterative expansions of them, much like how calculus builds upon algebra. The process allows for critical engagement with literary heritage while opening the door to voices historically silenced. These modern adaptations serve as pedagogical tools, cultural critiques, and forms of resistance against dominant narratives, demonstrating that the canon is not fixed but ever-expanding.